An acidless microwave-assisted wet digestion of biological samples as a greener alternative: applications from COVID-19 monitoring to plant nanobiotechnology - da Silva, Ana Beatriz Santos [UNESP]; da Silva Leal, Ketolly Natanne; Arruda, Marco Aurélio Zezzi (Springer Nature, 2025)
Sample preparation in an analytical sequence increases the number of errors, is highly time-consuming, and involves the manipulation of hazardous reagents. Therefore, when an improvement in an analytical method is required, the sample preparation step needs to be optimised or redesigned. Moreover, this step can involve significant toxic reagents and a high volume of waste. In that regard, this study proposes a new procedure based on microwave-assisted wet digestion combining two green strategies: a miniaturised system (with a few microlitres of volume) and the only use of hydrogen peroxide. Three biological samples (human serum, urine, and plant in vitro material) were chosen due to their high potential for disease monitoring, toxicological studies, and biotechnology applications. Several trace elements (Ca, Cd, Co, Cu, Fe, Mg, Mn, Mo, Ni, Se, and Zn) were determined by inductively coupled plasma optical emission spectroscopy and inductively coupled plasma mass spectrometry. For human serum and urine, a certified reference material was used to check for accuracy; the recovery ranged from 72% (Cd, ICP-MS) to 105% (Mg, ICP OES) for serum, while for urine, they varied from 82% (Ni, ICP-MS) to 122% (Zn, ICP-MS). For the soybean callus sample (in vitro plant material), a comparison between the proposed method and the acid digestion method was conducted to evaluate the accuracy, and the results agreed. The detection limits were 0.001–60 µg L−1 (lowest for Cd), thus demonstrating a suitable sensitivity. Moreover, the decomposition efficiency was demonstrated by determining the residual carbon, and a low amount was found in the final product digested (below 0.8% w v−1). A green metric approach was calculated for the proposed method, and according to AGREEprep software, it was found to be around 0.4. Finally, the method was applied to urine samples collected in patients with COVID-19 and soybean callus cultivated with silver nanoparticles. This sample preparation method is a new acidless and miniaturised alternative for elemental analysis involving biological samples.
Keywords: Biological samples; Green method; Hydrogen peroxide; In loco acid generation; Sample preparation